INTEGRASI PSIKOLOGI KELUARGA ISLAM DALAM KETAHANAN EMOSIONAL PASCAPERCERAIAN - Zaki Aqil Nashrullah; Taufik Hidayat (PT. Sulthan Journal Publisher, 2025)
Divorce affects not only legal relationships but also the emotional and spiritual stability of families. Many post-divorce individuals experience psychological distress, role disorientation, and difficulties in reconstructing life meaning. This article aims to analyze the integration of Islamic family psychology and modern psychological approaches in strengthening post-divorce emotional resilience. This study employs a qualitative library-based method with a normative-psychological analysis of family resilience theory, emotional regulation, and Islamic spiritual values. The findings indicate that post-divorce emotional resilience can be enhanced through adaptive emotional management, relational reconstruction, and spiritual reinforcement such as patience, trust in God, and self-purification. This integrative framework offers a relevant conceptual model for supporting emotional recovery among Muslim families in the Indonesian socio-religious context.